"We understand our community": implementation of the Healthy Eating Healthy Aging program among community-based organizations. Issue 2 (25th June 2020) - Leong, Judy; Jang, Sou Hyun; Bishop, Sonia K; Brown, Emily V R; Lee, Eun Jeong; Ko, Linda K
Abstract : Strategies for successful program implementation in community-based organizations serving older Asian Americans include stakeholder engagement, adaptation of program materials, and networking between organizations. Abstract: Cardiovascular disease is the second leading cause of death in the USA among Asian Americans and Pacific Islanders (AAPIs) over the age of 65. Healthy Eating Healthy Aging (HEHA), an evidence-based heart health program, can provide culturally appropriate nutrition education to decrease the risk of cardiovascular disease. Community-based organizations (CBOs) are optimal settings to implement community-based programs. However, there is inadequate research on how evidence-based interventions like HEHA are implemented in CBOs. This study examined processes that facilitated the implementation of HEHA among CBOs serving older AAPIs. Twelve representatives from CBOs that implemented the HEHA program were recruited to participate in a semistructured interview. All the participants were CBO directors or senior managers. A semistructured interview guide was created and informed by the Consolidated Framework for Implementation Research (CFIR) to capture how HEHA played into the five domains of CFIR: (a) intervention characteristics, (b) outer setting, (c) inner setting, (d) characteristics of the individuals, and (e) process. Data analysis captured themes under the CFIR domains. All five CFIR domains emerged from the interviews. Under intervention characteristics, three constructs emerged as facilitating the implementation of HEHA: (a) the participant's beliefs around the quality of the HEHA program and its ability to promote healthy eating, (b) HEHA's adaptability to different AAPI subgroups, and (c) perceptions of how successfully HEHA was bundled and assembled. Under outer setting, the participants described the community's need for healthy eating programs and how the HEHA program meets that need. Four constructs emerged under inner setting: (a) the CBO's structural characteristics and social standing in the community; (b) resources dedicated to the implementation and ongoing operations, including funding, training, education, physical space, and time; (c) the culture of the CBO; and (d) the participant's commitment and involvement in marketing, promotion, and implementation of HEHA. Under characteristics of individuals, participants' described their desire to learn the content of HEHA and deliver them successfully. Under process, participants described strategies to engage relevant individuals to facilitate HEHA implementation. The interviews with CBO representatives provided insights into CFIR domain constructs that facilitated the implementation of HEHA. CBOs are key settings for community health education. Understanding processes that lead to the successful implementation of evidence-based interventions among CBOs is critical for accelerating the dissemination and implementation of best practices.